rAAV expressing recombinant neutralizing antibody for the botulinum neurotoxin type A prophylaxis - Derkaev, Artem A.; Ryabova, Ekaterina I.; Esmagambetov, Ilias B.; Shcheblyakov, Dmitry V.; Godakova, Svetlana A.; Vinogradova, Irina D.; Noskov, Anatoly N.; Logunov, Denis Y.; Naroditsky, Boris S.; Gintsburg, Alexander L. (Frontiers in Microbiology, 2022)
Botulinum neurotoxin (BoNT) is one of the most dangerous bacterial toxins and a potential biological weapon component. BoNT mechanism of pathological action is based on inhibiting the release of neurotransmitters from nerve endings. To date, anti-BoNT therapy is reduced to the use of horse hyperimmune serum, which causes many side effects, as well as FDA approved drug BabyBig that consists of human-derived anti-BoNT antibodies (IgG) for infant botulinum treatment. Therapeutics for botulism treatment based on safer monoclonal antibodies are undergoing clinical trials. In addition, agents have been developed for specific prevention of botulism, but their effectiveness has not been proven. In this work, we have obtained a recombinant adeno-associated virus (rAAV-B11-Fc) expressing a single-domain antibody fused to the human IgG Fc-fragment (B11-Fc) and specific to botulinum toxin type A (BoNT/A). We have demonstrated that B11-Fc antibody, expressed via rAAV-B11-Fc treatment, is able to protect animals from lethal doses of botulinum toxin type A, starting from day 3 and at least 120 days after administration. Thus, our results showed that rAAV-B11-Fc is able to provide long-term expression of B11-Fc neutralizing antibody in vivo and provide long-term protection against BoNT/A intoxication. Consequently, our study demonstrates applicability of rAAV expressing protective antibodies for prevention of intoxication caused by botulinum toxins.